An automated in-situ polymerisation procedure for multi-functional cyanate ester resins via ring formation. (16th July 2021) - Demir, Baris; Hamerton, Ian
Abstract: Molecular dynamics simulations are valuable tools in enabling us to link molecular-level structure to macroscopic properties of new polymer-based materials. However, molecular simulation of cyanate ester polymers presents specific challenges, as a few credible procedures that captures ring formation is available. Despite the presence of previous attempts to this end, an automated process, that is easy to reproduce and adaptable for modelling cyanate esters, is still lacking. Herein, a robust and reproducible triazine ring formation procedure to reliably model, test, and tune polymer structures for use in molecular simulations is reported. In addition to being entirely reproducible, this procedure provides sufficient details to be applied to model polymers generated via ring formation between cyanate groups. Amongst our developments, key features include a reliable process for generating and equilibrating liquid samples to be polymerised, a robust ring formation algorithm, and establishment of a clear protocol to predict macroscopic properties such as glass transition temperature and Young's modulus of the polymerised samples. Predicted macroscopic properties agreed well with available experimental data. Our procedure provides a perfect platform for the process of modelling cyanate esters and can be easily adapted to generate porous polymers such as covalent organic frameworks. Graphical abstract: Image 1 Highlights: A computational procedure was developed to model, test and tune cyanate ester resins. Ring formation between cyanate ester monomers was captured on-the-fly. Thermo-mechanical properties were predicted as a function of degree of polymerisation. Cyanate ester monomers with varying number of aromatic rings showed distinct properties.